Representasi Gender dalam Laporan Tahunan Perusahaan Meliputi: Bukti dari Perusahaan LQ45 di Indonesia - Ummami, Latifa; Chandra Fitra Arifianto (LP3kM Buddhi Dharma University, 2025)
This study aims to analyze gender representation on the covers of annual reports of companies listed in the LQ45 on the Indonesia Stock Exchange. Annual report covers are understood not merely as visual identities but also as organizational communication media rich in symbolic meaning, reflecting the company's values, culture, and commitment to diversity. The method used is descriptive qualitative with visual content analysis of 45 annual report covers selected through purposive sampling. Human elements are divided into six groups: individual men, men with men, individual women, women with women, women with men, and non-human illustrations, which are then calculated for frequency and analyzed using gender equality and organizational communication theories. The results show that men are more dominantly represented, both individually and in pairs with other men (31%), while not a single cover features women as a single figure. Representations of women appear more frequently alongside men (40%) and only 2.2% within the female group, while 26.6% of covers feature non-human illustrations. Men's positions tend to be depicted as symbols of authority and leadership, while women are positioned as supporting figures. These findings indicate a symbolic invisibility of women in corporate communications, in line with Role Congruity Theory and global research on gender bias. This reflects the persistence of patriarchal structures in Indonesian corporate culture and highlights the gap between diversity policies and symbolic representation. Practically, the absence of balanced gender representation in visual communications has the potential to undermine a company's legitimacy in the eyes of global stakeholders and diminish its contribution to the principles of equality and sustainability.